Analisa Studi Kelayakan Website Dinas Kebudayaan Provinsi Riau Menggunakan Metode TELOS - Ramadani, Roby (Universitas Multi Data Palembang, 2024)
The implementation of a feasibility study is carried out to assess a system whether the system being developed is feasible or not to be implemented. Later in this paper an assessment will be carried out on the suitability of the Riau Province Culture Service website using the TELOS method. The TELOS method consists of five feasibility factors, namely technical feasibility, economic feasibility, legal feasibility, operational feasibility and schedule feasibility. One of the feasibility factors for TELOS is economic feasibility using Payback Period (PP), and Return of Investment (ROI). The process carried out in this test is conducting literature studies, determining test factors, carrying out feasibility tests, analyzing the results and formulating test results. Based on the evaluation results of the 5 feasibility factors, a final score of 8.2 was obtained, which means that the evaluation of the development of the Culture Service website is WORTH IT (B), with a low risk of development occurring, so the Riau Province Culture Service website is suitable for development. Keywords : Feasibility Study, Feasibility TELOS, Website Dinas Kebudayaan